Hearing Evaluation After Myringoplasty At Nepal Medical College And Teaching Hospital - Joshi, Rupesh Raj; Jha, Anil Kumar; Rijal, Anupama Shah; Dhungana, Anup; Shrestha, Kundan Kumar (Journal of Nobel Medical College, 2013)
Objective: To evaluate the graft takes rate of the myringoplasties performed by underlay technique using temporalis fascia graft for the last one year and to assess the hearing improvement in the successfully operated cases. Methods: This prospective Study included 52 ears of 50 patients, who underwent myringoplasty. All operations were performed using an underlay technique and mostly by postaural approach. In all the cases, temporalis fascia was used for the reconstruction of TM. The data of all the patients regarding preoperative disease, perforation size and localization, surgical approach, graft material, pre- and postoperative clinical and functional (hearing evaluation by pure-tone audiogram) results were analyzed. Results: Successful closure rate of the TM perforation was 82.69% and the graft failure rate was 17.30%. In this study, lowest and highest age of patients at presentation was 12 and 42 years respectively with a mean age of 25.5 years. The success rate was better with the advancing age. The most common approach was postaural. Medium size and posterior perforations were common and the graft take rate was 80.95%, and 88.89% respectively. The mean pre and post-operative air conduction threshold in the successful cases were 38.69dB and 30.35 dB respectively with a mean audiological improvement of around 8 dB. The improvement in the hearing was achieved in only 67.44% (29 out of 43) among the successful operated myringoplasties. Conclusion: Myringoplasty is a safe and effective technique to improve the quality of life of patients. The most common approach was postaural. The graft takes rate was better with the advancing ages and with the medium size and posterior perforations. The improvement in hearing was also achieved. Journal of Nobel Medical College Vol. 2, No.1 Issue 3 Nov.-April 2013 Page 36-42 DOI: http://dx.doi.org/10.3126/jonmc.v2i1.7671